The primary production and vegetation characteristics of some Pyrenean Aragonese meadows and their relationship with climate and management - Fillat F.; Goded L.; Pardo F.; Reine R.; Chocarro C.; Fanlo R. (Systèmes d'élevage et gestion de l'espace en montagnes et collines méditerranéennes, 1999)
Livestock production in the Spanish Pyrenees is of reduced importance compared with tourism and enjoyment of nature. To identify the potential for sustainable livestock production systems within a landscape where the primary aim is to create/maintain an attractive landscape rich in biodiversity, some studies were carried out in the Pyrenean Aragonese meadows. Studies on soil and vegetation related with climatic events were carried out in the private meadows of the village of Fragen (Broto valley). The floristic composition allows us to classify them into three management groups: (i) two cuts and grazing with irrigation; (ii) a single cut and grazing without irrigation; and (iii) grazing only.